2013
DOI: 10.1002/jmri.24367
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion restriction of the optic nerve in patients with acute visual deficit

Abstract: DWI can identify ischemic lesions of the optic nerve. As in acute multiple sclerosis lesions, optic neuritis can also present in rare circumstances with diffusion restriction and can therefore not be ruled out solely by DWI MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…It has been proposed that diffusion-weighted MR imaging may differentiate ischemic optic neuropathy from optic neuritis (6). In a recent study, diffusion-weighted imaging was abnormal in 5/5 patients with acute ischemic optic neuropathy, but only 2/25 patients with acute optic neuritis (7). The mean apparent diffusion coefficient was 0.55 × 10 -3 mm 2 /s in acute ischemic optic neuropathy and 1.10 × 10 -3 mm 2 /s in acute optic neuritis.…”
Section: Discussionmentioning
confidence: 94%
“…It has been proposed that diffusion-weighted MR imaging may differentiate ischemic optic neuropathy from optic neuritis (6). In a recent study, diffusion-weighted imaging was abnormal in 5/5 patients with acute ischemic optic neuropathy, but only 2/25 patients with acute optic neuritis (7). The mean apparent diffusion coefficient was 0.55 × 10 -3 mm 2 /s in acute ischemic optic neuropathy and 1.10 × 10 -3 mm 2 /s in acute optic neuritis.…”
Section: Discussionmentioning
confidence: 94%
“…18 The frequency of restricted diffusion in optic neuritis is not clear; however, one retrospective study found that 8% of patients with clinical optic neuritis showed restricted diffusion on DWI. 19,20 Furthermore, changes within the optic nerve are more commonly seen with gadolinium enhanced imaging, 20 a feature not usually associated with acute ischaemic lesions.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…83,84 Findings that would not be associated with typical optic neuritis would include a compressive lesion such as a meningioma, an optic nerve glioma or lymphoma, optic nerve sheath enhancement combined with other cranial nerve enhancement as seen in granulomatous disease such as sarcoidosis (Fig. 10), sequela of radiation therapy (Fig.…”
Section: Mukhi and Lincolnmentioning
confidence: 98%